Kontruksi Sosial dan Pendidikan Anak dalam Keluarga Pelaku Teroris - Arini Indah Nihayati (Bidayatuna, 2018)
This article discusses the phenomenon of the widespread involvement of children in acts of terrorism in Indonesia, especially those that occurred in 2018. Such phenomenon indicates that mothers and fathers involve their children in acts of terrorism. The research is conducted with Berger and Luckman’s social construction approach. In addition, Derrida's deconstruction theory is also employed to support the analysis. The result, based on Berger and Luckman’s social construction theory, this phenomenon occurs because of radical constructivism. Furthermore, employing Derrida's deconstruction theory, this research finds that such terrorism has tendency of deconstruction process that rejects all forms of establishment, absoluteness, standard and rigid values in society. This proves the dynamics of human diversity in the real sense. However, this can also lead to intolerance.